Dissecting Target Toxic Tissue and Tissue Specific Responses of Irinotecan in Rats Using Metabolomics Approach - Yao, Yiran; Zhang, Pei; Wang, Jing; Chen, Jiaqing; Wang, Yong; Huang, Yin; Zhang, Zunjian; Xu, Fengguo (Frontiers in Pharmacology, 2017)
As an anticancer agent, irinotecan (CPT-11) has been widely applied in clinical, especially in the treatment of colorectal cancer. However, its clinical use has long been limited by the side effects and potential tissue toxicity. To discriminate the target toxic tissues and dissect the specific response of target tissues after CPT-11 administration in rats, untargeted metabolomic study was conducted. First, differential metabolites between CPT-11 treated group and control group in each tissue were screened out. Then, based on fold changes of these differential metabolites, principal component analysis (PCA) and hierarchical cluster analysis (HCA) were performed to visualize the degree and specificity of the influences of CPT-11 on the metabolic profiles of 9 tissues. Using this step-wise method, ileum, jejunum and liver were finally recognized as target toxic tissues. Furthermore, tissue specific responses of liver, ileum and jejunum to CPT-11 were dissected and specific differential metabolites were screened out. Perturbations in Krebs cycle, amino acid, purine and bile acid metabolism were observed in target toxic tissues. In conclusion, our study put forward a new approach to dissect target toxic tissues and tissue specific responses of CPT-11 using metabolomics.